2014
DOI: 10.2139/ssrn.2383346
|View full text |Cite
|
Sign up to set email alerts
|

Financial Innovations, Money Demand, and the Welfare Cost of Inflation

Abstract: In the 1990s, the empirical relationship between money demand and interest rates began to fall apart. We analyze to what extent financial innovations can explain this breakdown. For this purpose, we construct a microfounded monetary model with a money market that provides insurance against liquidity shocks by offering short-term loans and by paying interest on money market deposits. We calibrate the model to U.S. data and find that the introduction of the sweep technology at the beginning of the 1990s, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 49 publications
(49 reference statements)
6
31
0
Order By: Relevance
“…6 Like in Williamson (2012), trade in the goods market is performed by money and claims to bonds. Williamson (2014a) focuses his analysis on an equilibrium where government bonds are scarce and thus are priced above their fundamental value.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…6 Like in Williamson (2012), trade in the goods market is performed by money and claims to bonds. Williamson (2014a) focuses his analysis on an equilibrium where government bonds are scarce and thus are priced above their fundamental value.…”
Section: Literaturementioning
confidence: 99%
“…Table 3 gives a brief overview of our results. 1 7 We follow the …ndings of Berentsen et al (2015a) and use M1 adjusted for retail sweeps instead of M1, because it represents the stock of transaction media more accurately. 1 8 Money demand is measured as the ratio of M1 adjusted for retail sweeps divided by the nominal gross domestic product.…”
Section: Numerical Examplementioning
confidence: 99%
“…The results from this literature are ambiguous. 9 There are a few theoretical papers that have studied the e §ects of a FTT. To our knowledge, only three papers investigated the implications of a FTT on welfare: Subrahmanyam (1998), Dow and Rahi (2000) and Dávila (2013).…”
Section: Literaturementioning
confidence: 99%
“…29 In this paragraph, we estimate the model's interest rate elasticity of money demand using a point approximation at the calibrated value of γ. In Berentsen et al (2014b) it is shown that when estimating the model's elasticity of money demand by ordinary least squares and a log-log specification, the standard errors are small. Thus, a point approximation at the calibrated value of γ represents a reasonable approximation for the model's elasticity of money demand.…”
Section: The Consumer's Bargaining Share In the Secondary Bond Marketmentioning
confidence: 99%
“…The basic setup follows Berentsen et al (2015). The main di¤erence is that we relax the full commitment assumption for …nancial transactions and study the implication of limited commitment for the shape of the money demand function.…”
Section: Environmentmentioning
confidence: 99%